Author Correction: Association analyses of more than 140,000 men identify 63 new prostate cancer susceptibility loci. - Schumacher,FR; Olama,AAA; Berndt,SI; Benlloch,S; Ahmed,M; Saunders,EJ; Dadaev,T; Leongamornlert,D; Anokian,E; Cieza-Borrella,C; Goh,C; Brook,MN; et al. (Nat Genet, 2019)
In the version of this article initially published, the name of author Manuela Gago-Dominguez was misspelled as Manuela Gago Dominguez. The error has been corrected in the HTML and PDF version of the article.